Determinants of suboptimal CD4+ T cell recovery after antiretroviral therapy initiation in a prospective cohort of acute HIV‐1 infection. Issue 9 (19th September 2020) - Handoko, Ryan; Colby, Donn J; Kroon, Eugène; Sacdalan, Carlo; de Souza, Mark; Pinyakorn, Suteeraporn; Prueksakaew, Peeriya; Munkong, Chutharat; Ubolyam, Sasiwimol; Akapirat, Siriwat; Chiarella, Jennifer; Krebs, Shelly; et al.
Abstract: Introduction: Up to 30% of individuals treated with antiretroviral therapy (ART) during chronic HIV fail to recover CD4 counts to >500 cells/mm 3 despite plasma viral suppression. We investigated the frequency and associations of suboptimal CD4 recovery after ART started during acute HIV infection (AHI). Methods: Participants who started ART in Fiebig I to V AHI with ≥48 weeks of continuous documented HIV‐RNA < 50 copies/mL were stratified by CD4 count at latest study visit to suboptimal immune recovery (SIR; CD4 < 350 cells/mm 3 ), intermediate immune recovery (IIR; 350 ≤ CD4 < 500) and complete immune recovery (CIR; CD4 ≥ 500). Clinical and laboratory parameters were assessed at pre‐ART baseline and latest study visit. Additional inflammatory and neurobehavioral endpoints were examined at baseline and 96 weeks. Results: Of 304 participants (96% male, median 26 years old) evaluated after median 144 (range 60 to 420) weeks of ART initiated at median 19 days (range 1 to 62) post‐exposure, 3.6% (n = 11) had SIR and 14.5% (n = 44) had IIR. Pre‐ART CD4 count in SIR compared to CIR participants was 265 versus 411 cells/mm 3 ( p = 0.002). Individuals with SIR or IIR had a slower CD4 rate of recovery compared to those with CIR. Timing of ART initiation by Fiebig stage did not affect CD4 count during treatment. Following ART, the CD8 + T cell count ( p = 0.001) and CD4/CD8 ratio ( p = 0.047) were lower in SIR compared to CIR participants. Compared to the CIR group at week 96, the combined SIR and IIR groups had higher sCD14 ( p = 0.008) and lower IL‐6 ( p = 0.04) in plasma, without differences in neuropsychological or psychiatric indices. Conclusions: Despite immediate and sustained treatment in AHI, suboptimal CD4 recovery occurs uncommonly and is associated with low pre‐ART CD4 count as well as persistent low CD8 count and CD4/CD8 ratio during treatment.